Exotic Metamaterials from Noncommutative Theory. Issue 9 (18th July 2018) - Prudencio, Thiago; Belich, Humberto
Abstract: Exotic optical properties in materials are investigated as a consequence of noncommutative geometry (NCG) originated from deformed Heisenberg algebra. The NCG leads to modified eletromagnetism and then changes the constitutive relations that allow the determination of refractive index and impedance of the medium for different materials. Considering different situations where permittivity and permeability are obtained depending on NCG parameters, in dielectric, nonmagnetic, and magnetic cases, exotic conditions associated with metamaterial properties are obtained as the presence of negative index refraction under a generalized susceptibility depending on NCG. These results show that a class of optical metamaterials can be modeled based on NCG depending on noncommutative parameters. Abstract : Exotic metamaterials are built based on noncommutativity . Modified electromagnetism and negative index refraction in this scenario are discussed. Different situations where permittivity and permeability in dielectric, nonmagnetic and magnetic cases are obtained depending on noncommutative geometry (NCG) parameters are discussed. Exotic conditions associated with metamaterial properties depending on NCG are discussed. Optical metamaterials are modeled with dependence on noncommutative parameters.